CONTEXT-BASED TASKS IN MATHEMATICS AS A MEANS OF DEVELOPING FUNCTIONAL LITERACY OF STUDENTS - Batyrbayeva , Г.; Assanova , А.Т.; Bauash , Г.Е. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article considers the solution of contextual problems in mathematics lessons at school as an effective means of developing functional literacy of students and describes its impact on the conditions of everyday life. The relevance of the article is due to the fact that the intensive application of mathematical knowledge not only in various fields of science but also in everyday life requires addressing the issue of the need to form functional mathematical literacy of students, starting from school. The result of modern education is determined by such skills as the orientation in information flows, analysis, application and transformation of knowledge, ensuring the independent acquisition of new and continuous knowledge by an individual. All this defines the essence of the concept of functional literacy. Mathematical literacy is an integral part of it. To achieve such educational results, students should more often solve contextual problems that reveal the scientific content of mathematics, its specifics, and its connection with other subjects. In general, the applied nature of contextual tasks for students is helpful in solving problems of real life and everyday situations. The article focuses on the definition of contextual tasks, their levels and methods. The results of the secondary school students survey relevant to the research topic were determined by a diagram. Based on the results, the optimal and vulnerable moments of contextual learning are considered and ways to solve are shown.